Concurrent regenerating codes. Issue 3 (1st February 2017) - Zhang, Huayu; Li, Hui; Shum, Kenneth W.; Hou, Hanxu; Robert Li, ShuoYen
Abstract : To reduce multiple‐failure repair traffic in erasure coded storage systems, Patrick Lee et al. introduce concurrent framework‐based minimal‐storage regenerating codes (RGCs). The approach is simpler and more practical than the cooperative mechanism in non‐fully distributed environment. This study unifies such class of codes as concurrent RGC and further studies the characteristics by analysing the cut‐based information flow graph. The authors present a general storage–bandwidth tradeoff and give closed‐form expressions for the points on the curve including the minimal‐bandwidth point. They show that the concurrent RGC can be constructed by reforming the existing single‐node RGC or multiple‐node cooperative RGC. Moreover, a connection to strong‐maximum distance separable is also analysed.